Information and Organization for Horizontal Multimarket Coordination - Anand, Krishnan S.; Mendelson, Haim (Management Science, 1997)
We model the effects of alternative coordination structures on the performance of a firm that faces uncertain demand in multiple horizontal markets. The firm's coordination structure is jointly determined by its decision-rights structure and by its information structure. We compare the performance of decentralized, centralized and distributed structures and study factors that affect the value of coordination. The results quantify and illustrate the value of co-locating decision rights with specific knowledge.